Seasonal physico-chemical attributes of the river Buriganga, Turag and Balu, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2016)
Seasonal physico-chemical attributes (pH, EC, TSS, TDS, DO, BOD, COD, Cl, HCO3, NO3-N, NH4-N, Na, K, Ca, Mg, Fe, Zn, Cu, Ni, Al, Pb, Cd, Cr, and Hg) of the river Buriganga, Turag and Balu have been studied to determine the pollution level of these rivers. It was revealed that most of the attributes exceeded the standard values set by GOB. Specially the parameters measured for the river Buriganga and Turag were in danger level. The level of pollution was much higher in winter and summer seasons compared to monsoon.Jahangirnagar University J. Biol. Sci. 3(1): 9-16, 2014 (June)